Ley Fundamental de Educación. Decreto 262-2011. Gaceta # 32,754. 22 de Febrero del 2012 - La Editora (La Revista de Derecho, 2013)
DOI: http://dx.doi.org/10.5377/lrd.v33i0.1264 Revista de Derecho, Vol. 33, Nº 1, Año 2012: 129-158